2018
DOI: 10.18410/jebmh/2018/221
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Outcome of Antenatal Hydronephrosis- An Integrated Clinical Approach

Abstract: BACKGROUNDThe widespread use of ultrasonography during pregnancy has resulted in a higher detection rate of congenital malformations. Out of these antenatally detected congenital malformations Antenatal Hydronephrosis (ANH) is the commonest one. The diagnosis of ANH causes significant distress to the parents. There always remains a probability of the neonate having complete resolution to undergoing surgery based on the degree of hydronephrosis measured primarily with AP diameter of renal pelvis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The current study findings are consistent with that of a previously published study showing that ANH resolved in 41.2% of patients and reached a good prognosis within two months with a value of 48.4% of participants exhibited good prognosis [12]. Altogether, our study and the studies by Kari et al and Chaudhary and Shah suggest that the outcome is possibly affected by the severity of ANH [12,26].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study findings are consistent with that of a previously published study showing that ANH resolved in 41.2% of patients and reached a good prognosis within two months with a value of 48.4% of participants exhibited good prognosis [12]. Altogether, our study and the studies by Kari et al and Chaudhary and Shah suggest that the outcome is possibly affected by the severity of ANH [12,26].…”
Section: Discussionsupporting
confidence: 93%
“…The finding that there was a relationship between patients who exhibited a UTI, with one or more associated conditions, such as VUR, and UPJO, and ANH prognosis could indicate that the presence of multiple ANH-associated comorbidities may increase the burden on health and thereby decrease overall ANH outcomes. Nevertheless, it is important to note that a previous study reported a poor correlation between VUR grade and ANH severity, suggesting that there might be nuances to this connection, which have yet to be discovered [26]. It is possible that including VUR grading into the current study would have yielded more definitive results and addressed this potential discrepancy.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Fifty to ninety percent of cases of mild hydronephrosis tend to resolve within the first two months of age. 6,8, 10 Others are caused by severe structural issues such as pelvic-ureteric junction (PUJ) obstruction, posterior urethral valve (PUV) or vesicoureteral reflux (VUR). 6 Although Mild renal pelvis dilatation is typically incidental and benign, it is a frequent and generic observation that can also be linked to structural and genetic problems.…”
Section: Introductionmentioning
confidence: 99%